Beak fracture associated with leiomyosarcoma in a budgerigar (Melopsittacus undulatus): a case report and literature review - Rasche, Brittany L.; Barrantes Murillo, Daniel Felipe; Negrão Watanabe, Tatiane Terumi (Frontiers in Veterinary Science, 2023)
A 2-year-old male budgerigar (Melopsittacus undulatus) died after a 1-day history of fracture of the rostral rhinotheca with pale mucous membranes, dyspnea, dull mentation, and ataxia. Histopathology revealed an infiltrative neoplasm composed of interweaving streams of spindle cells effacing the dermis and bone of the rostral upper beak as well as a ganglion and two cranial nerves. No visceral metastasis was observed. Neoplastic cells exhibited strong cytoplasmic immunolabeling for alpha-smooth muscle actin (α-SMA) and lacked immunolabeling for S100, Melan-A, PNL2, and cytokeratin AE1/AE3. These findings were consistent with a locally invasive leiomyosarcoma Leiomyosarcomas arise from the smooth muscle and are locally invasive with rare metastases. In birds, leiomyosarcomas are mostly reported to arise from the spleen, gastrointestinal, and reproductive tracts. In the case report herein, we describe the histological and immunohistochemical features of a primary beak leiomyosarcoma in a budgerigar associated with a fracture located at the rostral rhinotheca. Leiomyosarcoma arising from the beak has not been described in the literature.